Greek Naval Strategy and Policy 1910-1919. - Fotakis, Zisis (Cass series--naval policy and history., 2008)
A sharp analysis of Greek naval history in the 1910s, a time when the importance of its geographic position and its navy increased greatly. It explains the causes of these developments and their consequences for Greek national aims, the Mediterranean naval situation and the Balkan balance of power. Within this context, it also examines the competition between Britain, France, and Germany for Greek naval procurements and influence, Greek-Turkish naval tensions and the responses of the great powers. This volume also provides an in-depth analysis of the naval strategy, programme, education and or.